Influence of Work Values on the Prescribing Behavioral Intentions Regarding Antibiotic Use Among Primary Physicians in Hubei, China - Lu, Junyu; Liu, Chenxi; Wang, Dan; Zhang, Xinping (Frontiers in Public Health, 2022)
Objective: Primary physician has been an important cause of global antibiotic resistance. The aim of this study is to identify the influence of primary physicians’ work values on prescribing behavioral intentions regarding antibiotic use (behavioral intentions). Methods: A total of 656 primary physicians’ work values and behavioral intentions were collected by a stratified cluster sampling from 67 primary care facilities in Hubei Province of China. Work values included 5 dimensions, namely intrinsic values, extrinsic values, reward values, social values and altruistic values. Behavioral intentions included 2 dimensions of the intentions to reduce antibiotic prescriptions and the intentions to prescribe antibiotics. A Likert five-point scale was used and higher scores meant greater intentions to prescribe antibiotics. A hierarchical multiple regression analysis was employed to model the influence of work values on behavioral intentions. Results: Primary physicians’ behavioral intention was 2.01 averagely. Intrinsic values negatively influenced overall intentions to prescribe more antibiotics (β = -0.098, P = 0.010). And lower social values perception (β = 0.248, P < 0.001), less pursuit of reward values (β = 0.194, P<0.001), and less emphasis on altruistic values (β = 0.180, P < 0.001) positively influenced lower overall intentions to prescribe antibiotic prescriptions. Besides, extrinsic values were not found influencing the behavioral intentions (β = 0.001, P = 0.961). Conclusions: Primary physicians’ work values influenced their behavioral intentions regarding antibiotic use. Training and education of work values may be an entry point for intervention on improving antibiotic prescribing.